HAK-HAK KEWARISAN BANCI DALAM HUKUM ISLAM - Umar, Subehan Khalik (Al-Daulah : Journal of Criminal Law and State Administration Law, 2017)
Islamic jurisprudence has placed a sissy as one of the legalphenomena and their existence has made the study of Islamic law inthe field of inheritance to be more comprehensive. The sissy (khunṣa)in Islamic inheritance law is only pinned to those who have multiplegenitals. They are then identified based on the function of bothgenitals and defined their status based on the determination. Thosewho fail to pass through this process are then punished as animproper (muskilate) sissy. This group will get the smallest portion ofinheritance from their portion while awaiting research on their finalgender.